Optimizing care for children with difficult-to-treat and severe asthma through specialist paediatric asthma centres: expert practical experience and advice - Pijnenburg, M. W. (BioMed Central, 2026)
Severe asthma in children carries an unacceptable treatment burden, yet its rarity means clinical experience in treating it is limited, even among specialists. Practical guidance is needed to support clinical decision-making to optimize treatment for children with this condition.This modified Delphi convened 16 paediatric pulmonologists and allergologists from northern Europe, all experienced in treating children with severe asthma. Informed by interviews with stakeholders involved in the care of children with severe asthma (including paediatricians, nurses and carers), and an analysis of European guidelines, the experts built a consensus focused on the gaps in existing guidance. Explored were considerations for optimizing care for patients needing biologic treatment, and for selecting home or hospital delivery of biologics. This consensus is aimed at clinicians in specialist centres, as well as general paediatricians, paediatric allergologists and paediatric pulmonologists who refer children with the most severe asthma to specialist care. Consensus is based on expert opinion and is intended for use alongside published guidelines.Our discussions revealed three key facets to optimizing care. Firstly, early asthma detection in children presenting with wheezing and/or dyspnoea is vital, with a low threshold for referral from primary to specialist care. Secondly, children who may need biologics should be referred to and managed by specialist paediatric asthma centres; we define principles for the specialist team members, tests, and expertise necessary at such centres, as well as guidance on when homecare biologics delivery is and is not appropriate. Thirdly, shared decision-making is essential at all stages of the patient's journey: clear, concise treatment plans are vital for patient/carer self-management, and structured processes for transition from paediatric to adult services are valuable. The experts identified the potential for specialist paediatric asthma nurses to play a significant role in facilitating multidisciplinary working.Through this project is agreed a framework of practical advice to optimize the care of children with severe asthma. We encourage clinicians and policymakers to implement this practical advice to enhance patient care.